An Integrated Genetic and Physical Map for the Malaria Vector Anopheles funestus - Wondji, Charles S. (Copyright © 2005 by the Genetics Society of America, 2005)
We have constructed a genetic map of the major African malaria vector, Anopheles funestus, using genetic markers segregating in F(2) progeny from crosses between two strains colonized from different field sites. Genotyping was performed on 174 progeny from three families using 33 microsatellite markers, a single RFLP, and 15 single nucleotide polymorphism (SNP) loci. Four linkage groups were resolved and these were anchored to chromosomes X and 2 and chromosomal arms 3R and 3L by comparison with a physical map of this species. Five markers were linked to the X chromosome, 16 markers to chromosome 2, and 10 and 11 markers to chromosomal arms 3R and 3L, respectively. This significantly increases the number of chromosomally defined genetic markers for this species and will facilitate the identification of genes controlling epidemiologically important traits such as resistance to insecticides or vector competence.